2011
DOI: 10.1007/s12043-011-0170-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non-uniform interfacial tension in small Reynolds number flow past a spherical liquid drop

Abstract: A singular perturbation solution is given for small Reynolds number flow past a spherical liquid drop. The interfacial tension required to maintain the drop in a spherical shape is calculated. When the interfacial tension gradient exceeds a critical value, a region of reversed flow occurs on the interface at the rear and the interior flow splits into two parts with reversed circulation at the rear. The magnitude of the interior fluid velocity is small, of order the Reynolds number. A thin transition layer atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…1 (b). For this geometry there exists a solution of the Stokes equation for the fluid flow field inside and outside of the droplet as well as the fluid velocity at the interface [35,36]. The solution at the interface is given in terms of the surface tension gradient: n+1 (z).…”
Section: Diffusion-advection-reaction Equationmentioning
confidence: 99%
“…1 (b). For this geometry there exists a solution of the Stokes equation for the fluid flow field inside and outside of the droplet as well as the fluid velocity at the interface [35,36]. The solution at the interface is given in terms of the surface tension gradient: n+1 (z).…”
Section: Diffusion-advection-reaction Equationmentioning
confidence: 99%
“…In the proximity of the droplet interface, Marangoni flow is directed towards increasing surface tension. So far, there have been detailed studies of the flow field around active droplets, where the surface tension is axisymmet-ric σ = σ(θ) 38,39 . Formulas of the non-axisymmetric case have been mentioned in an extensive study of the rheology of emulsion drops and have been used to explain cross-streamline migration of emulsion droplets in Poiseuille flow [40][41][42] .…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly for , although the external stresslets enlarge due to inertial effect, which successively enhances the interfacial stress (see figure 2 b ), the migration velocity increases with . This is due to the existence of prominent counter rotating vortices of the interior flow in the direction of migration of the droplet (see figure 3 c ), which re-acclimate and retaliate the enhanced stress at finite (Mason & Moremedi 2011). In this regard, we note that the previous counteraction for is inconceivable for an equivalent solid squirmer (with ).…”
Section: Results: First-order Correctionmentioning
confidence: 92%
“…Wu et al (2009) have demonstrated kinematic separation of mixed bacteria streaming against a wall and shown that the larger bacteria have a faster rate than the smaller bacteria. However, there exist preferably a limited number of studies that have quantified the effects of convective inertia on the kinematics and energetics of swimming droplets (Li & Mao 2001; Mason & Moremedi 2011) which are potential artificial analogues of biological systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation